TINGKAT KEPUASAN PASIEN RAWAT INAP TERHADAP PELAYANAN KONSELING GIZI DI RUMAH SAKIT PUSAT OTAK NASIONAL - Yessi Marlina; Asti Ramadhani (Poltekkes Kemenkes Mataram, 2021)
Background : Nutrition counseling is a two-way communication process between counselor and client to help clients recognize and overcome nutritional problems. Patients are entitled to receive a good quality nutrition counseling since that is an integral part in accelerating the patient's healing process. The purpose of this study was to determine the level of satisfaction of patients with nutrition counseling services at the Rumah Sakit Pusat Otak Nasional. Methods : This research was a descriptive study with cross sectional design. The sample technique used accidental sampling with total samples were 30 patients from second and third-grade room. The level of satisfaction included counseling service time, attitudes and characteristics of counselor, materials of counseling and media of counseling. Response options were based on a five-point Likert scale from “strongly satisfied” to “strongly unsatisfied”. Results : The results showed that the satisfaction rate with counseling service time was 77,06% (satisfied), attitudes and characteristics of counselor was 84,26% (very satisfied), counseling material was 78,13% (satisfied), and the use of media during the nutritional counseling process was 65,86% (satisfied). Conclusion : The satisfaction rate with nutritional counseling services at the Rumah Sakit Pusat Otak Nasional is satisfied (73,33%).